Islamic finance in China: current landscape and future forward - Hao, Yan; Haji Yahya, Mohamed Hisham; Latip, Malisah; Ali, Muhammad Hafiz (Universiti Sains Islam Malaysia, 2022)
China’s foreign trade has gradually lost its advantage due to continuous rise of RMB exchange rate and the labor costs in recent years. China urgently needs to explore new international trade markets to reinvigorate its foreign trade. With the recent development strategy of “One Belt One Road”, China should seize this opportunity to develop Islamic finance since most countries along the routes are Islamic countries. Islamic finance differs from traditional finance in its principles, development, products, operations, and regulation. The purpose of this article is to examine Chinese views on Islamic finance. The study conducted a survey through questionnaire. The findings show that the most ideal area to develop Islamic finance is in China’s northwest region due to its cultural advantages. The survey records that respondents’ reluctance towards Islamic finance mainly due to the absence of legal system and financial regulations for Islamic finance in China. Moreover, lack of talents in Islamic finance is also a major concern based on the survey. The study believes that the development of Islamic finance is conducive to the sound development of China’s financial system. It strengthens economic and trade cooperation with the Islamic world, enhances the ability to attract investment, and promotes harmonious economic development of ethnic minority areas.